Tru & Nelle : a novel - Neri, Greg (Boston ; New York : Houghton Mifflin Harcourt, 2016)
In their small town of Monroeville, Alabama, in 1930, misfits Tru and Nelle strike up a friendship and find a mystery to solve when someone breaks into the drugstore and steals some candy and a fancy brooch.
Tru & Nelle -- Other stories. The case of the missing plane ; Sook's secret recipe ; Archulus Persons is a big fat liar ; A monster fish and the two-headed chicken ; The very first time I ever laid eyes on Truman ; The road to Monroeville.
Keywords: Capote, Truman, -- 1924-1984 -- Juvenile fiction; Lee, Harper -- Juvenile fiction; Capote, Truman, -- 1924-1984 -- Fiction; Lee, Harper -- Fiction; Friendship -- Fiction; Mystery and detective stories; Monroeville (Ala.) -- History -- 20th century -- Fiction; Friendship -- Fiction; Detective and mystery fiction